Analisis Peran Corporate Social Responsibility (CSR) dalam Membangun Citra Positif Bank Syariah di Indonesia - Mujib, Muhammad Abdul (Program Studi Perbankan Syariah STAI Senori Tuban, 2025)
This research examines the role of Corporate Social Responsibility (CSR) in shaping a positive image of Islamic banks in Indonesia, employing a literature review approach to gather and analyze various relevant literature sources. The thematic analysis method was applied to identify patterns and themes that emerged from data related to CSR implementation and public perceptions of Islamic banks. The research results indicate that effective CSR implementation not only enhances the image and reputation of Islamic banks but also fosters customer loyalty and public trust. CSR programs that focus on economic empowerment, education, and health have been proven to have a significant positive impact, as well as creating mutually beneficial relationships between banks and the community. Thus, the integration of CSR in the business strategy of Islamic banks is very important for long-term sustainability and growth.